Adolescent resilience: - - Alcalá Martinez, Susana Berenice (2025)
Adolescence is a stage in human development, it is characterized by the search for identity and experimentation, which sometimes leads to tobacco consumption. The habit of smoking tobacco, influenced by social, family and emotional factors, is a health risk. In this context, resilience, the ability to overcome adversity and resist social pressures, plays a fundamental role in the prevention and reduction of tobacco consumption in adolescents. Interventions to smoking use in this population are educational and behavioral interventions. From a nursing perspective, the implementation of prevention and support interventions is essential. In this sense, school nurses have an important role in being an agent that facilitates change, providing evidence-based information, facilitating resilience skills and promoting healthy lifestyles.